A Visualization Approach to Analyze Android Smartphone Data - Nurul Adhlina Hani Roslee; Nurul Hidayah bt Ab Rahman (Politeknik Negeri Padang, 2018)
This study aims to design and develop an interactive system that can visualize evidence collected from Android smartphone data. This project is developing to support forensic investigator in investigating the security incidents particularly involving Android smartphone forensic data. The used of smartphone in crime was widely recognized. Several types of personnel information are stored in their smartphones. When the investigator analyses the image data of the smartphone, the investigator can know the behaviour of the smartphone’s owner and his social relationship with other people. The analysis of smartphone forensic data is cover in mobile device forensic. Mobile device forensics is a branch of digital forensics relating to recovery of digital evidence from a mobile device under forensically sound condition. The digital investigation model used in this project is the model proposed by United States National Institute of Justice (NIJ) which consists four phases, which are collection phase, examination phase, analysis phase and presentation phase. This project related with analysis phase and presentation phase only. This paper introduces Visroid, a new tool that provides a suite of visualization for Android smartphone data.